Case report of a pelvic-peritoneal tuberculosis presenting as an adnexial mass and mimicking ovarian cancer, and a review of the literature - (:unkn) unknown (My University, 2004)
[No abstract available]
Keywords: Adnexial mass; Ascites; CA 125; Ovarian cancer; Pelvic tuberculosis